Estudo experimental em ratos submetidos à injeção intravascular de polimetilmetacrilato: avaliação clínica e da toxicidade sistêmica - Medeiros, Clarissa Castro Galvão (2013)
Dermal fillers are being vastly applied at the face region in an attempt to achieve aesthetic or functional repair. When used inadvertently those products may promote a variety of adverse effects, sometimes involving the dentists anatomical area of expertise. Occasionally these complications suggest an incorrect clinical diagnosis since it can simulate other types of pathologies. These materials are distinct and may contain in its composition biological fragments, suspensions of particles or microspheres, for example. The technique of implantation and the possible outcomes are specific of the type of substance. Once these products are inserted into the tissues or accidentally inside of a blood vessel, local and/or systemic migration of the particles may occur. The polymethylmethacrylate (PMMA) is one of aesthetic filling materials of greater employment in Brazil, being broadly used in tissues of the facial and perioral region. The choice to use these products is encouraged by its low financial cost, long time of duration and simple technique of implantation. This research aimed to evaluate, in a murine model, the local reaction and possible systemic toxicity caused by intravascular injection of PMMA in two extreme concentrations (2 and 30%) that are often applied. The animals were randomly divided into 3 groups (2%PMMA, 30%PMMA and control) and 2 observation times (7 and 90 days). The material (0.05 mL) was applied into the ranine vein located at the ventral surface of the tongue on the right side. Lesions were not observed during clinical evaluation of the tongues at any time of the study. There was no presence of microspheres or inflammation in distant organs (liver, right lung and kidney) during microscopic evaluation. The levels of aspartate aminotransferase (AST) and creatinine were not significantly different between groups at any time of the study. Group 2 (30% PMMA) showed higher levels of alanine aminotransferase (ALT) at day 90 when compared to the other groups. It could be assumed that PMMA's higher concentration induced statistically significant change in ALT levels compared with the control group over time (P = 0.047). The variation in the weight of the organs has not demonstrated that the changes were related to signs of toxicity to PMMA. Faced with several reports of adverse effects from injections of PMMA in the lower face, especially nasolabial region it is of great importance that dentists are able to identify and manage possible complications. The lack of scientific data regarding local and systemic adverse effects related to cosmetic fillers containing PMMA, motivated this study and should be a stimulus for this issue to be addressed in further research in order to achieve a better comprehension about this subject. The data obtained in this study do not confirm that PMMA fillers have a potential toxic effect, after an intravascular injection, at the concentrations studied.